P029: Are acute pain trajectories after an emergency department visit associated with chronic pain at 3 months?. (May 2019) - Daoust, R.; Paquet, J.; Cournoyer, A.; Piette, E.; Morris, J.; Lessard, J.; Castonguay, V.; Lavigne, G.; Chauny, J.
Abstract : Introduction : Studies suggest that acute pain evolution after an emergency department (ED) visit has been associated with the development of chronic pain. Using group-based trajectory modeling (GBTM), we aimed to evaluate if ED discharged patients with similar pain intensity profiles of change over 14 days are associated with chronic pain at 3 months.Methods : This is a prospective cohort study of patients aged 18 years or older who visited the ED for an acute pain condition (≤2 weeks) and were discharged with an opioid prescription. Patients completed a 14-day diary in which they listed their daily pain intensity level (0-10 numeric rating scale). Three months post-ED visit, participants were interviewed by phone to report their pain intensity related to the initial pain.Results : A total of 305 patients were retained at 3 months (mean age ± SD: 55 ± 15 years, 49% women). Using GBTM, six distinct pain intensity trajectories were identified during the first 14 days of the acute pain period; two linear one with moderate or severe pain during the follow-up (representing almost 40% of the patients) and four cubic polynomial order trajectories, with mild or no-pain at the end of the 14 days (low final pain). Twelve percent (11.9; ±95%CI: 8.2-15.4) of the patients had chronic pain at 3 months. Controlling for age, sex and types of pain condition, patients with trajectories of moderate or severe pain and those with only severe pain were 5.1 (95%CI: 2.2-11.8) and 8.2 (95%CI: 3.4-20.0) times more likely to develop chronic pain at 3 months, respectively, compared to the low final pain group.Conclusion : Trajectories could be useful to early identification of patients at risk of chronic pain.